2016
DOI: 10.21608/bvmj.2016.31405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grilling on Pesticides Residues in O. niloticus Muscles

Abstract: Thirty six random healthy Oreochromusnilotica (O. niloticus) collected from Manzala Lake, wild Nile River "El-Ryiah El-Tawfiky", El-Abbasa private fish farm and Gesrbahr el-baar agricultural drainage (9 fish from each source). Concentrations of organochlorine pesticide residues (OCPs) were investigated in both raw and grilled fish (dry heat treatment). Fish musculature samples were analysed for detection the effect of grilling on level of organochlorine pesticides residues. Examination revealed that, samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However, El-Sherif (2017) reported that the highest loss of OCPs was observed for samples that cooked by boiling followed by frying and grilling, the average of total loss were 80.2 and 78.3% in boiled silver carp and catfish samples, respectively and total loss were 60.6 and 54.3% of fried samples and 39.0 and 32.1% of grilled fish samples, respectively. Also, our results are in agreement with many authors (Trotter et al, 1989;Zabik et al, 1995;Witczak, 2009;El-Sherif et al, 2016;Hassanen et al, 2016;El-Sherif, 2017 andSalah Eldin et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, El-Sherif (2017) reported that the highest loss of OCPs was observed for samples that cooked by boiling followed by frying and grilling, the average of total loss were 80.2 and 78.3% in boiled silver carp and catfish samples, respectively and total loss were 60.6 and 54.3% of fried samples and 39.0 and 32.1% of grilled fish samples, respectively. Also, our results are in agreement with many authors (Trotter et al, 1989;Zabik et al, 1995;Witczak, 2009;El-Sherif et al, 2016;Hassanen et al, 2016;El-Sherif, 2017 andSalah Eldin et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with that reported by Abd-Allah (2013) whom found that the loss rates of OCPs ranged from 18.40 -53.24% in fried, 12.8 -40.15% in grilled tilapia muscles from Nile River. Hassanen et al (2016) decided that the OCPs of Oreochromus niloticas collected from Manzala Lake were reduced by ratio of 11% -100% by grilling process. Similar results were reported by Eid and Salem (2012) who found that OCPs concentrations (α-HCH, γ-HCH and Endrin) were decreased in Tilapia nilotica samples after frying by 85, 79 and 80% respectively and by grilling 87, 52 and 100%, respectively, while, in Clarias lazera samples the levels decreased by 100, 54 and 83%, respectively by frying and 100, 50 and 100, respectively by boiling.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were detailed by Hassanen FS, et al [62], who studied the effect of the grilling cooking method on OCPs concentrations in raw Nile tilapia (Oreochromus nilotica) collected from three different areas. The results showed a significant decrease in OCPs concentrations by a ratio of 11% to 100% by grilling depending upon the type of pesticide residue and variation in localities.…”
Section: The Effect Of Traditional Cooking Methods On Pesticide Residuesmentioning
confidence: 88%